2016
DOI: 10.3389/fmicb.2016.01773
|View full text |Cite
|
Sign up to set email alerts
|

A Narrow pH Range Supports Butanol, Hexanol, and Octanol Production from Syngas in a Continuous Co-culture of Clostridium ljungdahlii and Clostridium kluyveri with In-Line Product Extraction

Abstract: Carboxydotrophic bacteria (CTB) have received attention due to their ability to synthesize commodity chemicals from producer gas and synthesis gas (syngas). CTB have an important advantage of a high product selectivity compared to chemical catalysts. However, the product spectrum of wild-type CTB is narrow. Our objective was to investigate whether a strategy of combining two wild-type bacterial strains into a single, continuously fed bioprocessing step would be promising to broaden the product spectrum. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 44 publications
2
130
3
Order By: Relevance
“…CO metabolites are involved in chain elongation reactions. Microbial elongation of acetate (2 carbons) to propionate (3 carbons), butyrate (4 carbons), and MCFA using H 2 :CO 2 and/or ethanol as electron and carbon donors has been demonstrated (Diender, Stams, & Sousa, ; Grootscholten, Kinsky dal Borgo, Hamelers, & Buisman, ; Richter, Molitor, Diender, Sousa, & Angenent, ; Steinbusch et al, ). The stoichiometry of these elongation reactions and the corresponding ΔG°′ values (kJ/e − equivalent) are summarized in Table S2.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CO metabolites are involved in chain elongation reactions. Microbial elongation of acetate (2 carbons) to propionate (3 carbons), butyrate (4 carbons), and MCFA using H 2 :CO 2 and/or ethanol as electron and carbon donors has been demonstrated (Diender, Stams, & Sousa, ; Grootscholten, Kinsky dal Borgo, Hamelers, & Buisman, ; Richter, Molitor, Diender, Sousa, & Angenent, ; Steinbusch et al, ). The stoichiometry of these elongation reactions and the corresponding ΔG°′ values (kJ/e − equivalent) are summarized in Table S2.…”
Section: Introductionmentioning
confidence: 99%
“…Production of caproate and alcohols from syngas (CO with H 2 and CO 2 ) was recently demonstrated by a syngas‐enriched mixed culture (Ganigué, Sánchez‐Paredes, Bañeras, & Colprim, ), and in pure culture studies (Gildemyn et al, ). In addition, co‐culture experiments have shown that CO can be converted to ethanol and then to MCFA in a controlled environment (Diender et al, ; Richter et al, ). However, the environments required for each step are not ideal for the opposite microbial partner, posing large challenges to further optimization and scale‐up with the co‐culture process (Diender et al, ; Richter et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diender et al and Richter et al have recently shown that a direct conversion of syngas to n -caproic acid with a co-culture of a carboxydotrophic bacterium and C. kluyveri is also possible [51, 57]. However, they found that a pH discrepancy exists between the two members in the co-culture, and that n -caproic acid was further reduced to n -hexanol, resulting in a low specificity for either product.…”
Section: Resultsmentioning
confidence: 99%
“…Interspecies complementary metabolism occurs whereby the products of one Clostridium are the substrates of another Clostridium and this is very prevalent in Clostridium present within the SFB ecosystem (Figure ). For example, C. ljungdahlii was able to cometabolize CO 2 and H 2 to acetate and ethanol, which can be used for the production of butyrate and caproic acid by C. kluyveri (Richter, Molitor, Diender, Sousa, & Angenent, ). Another synergistic interaction is the interspecies hydrogen transfer (Thauer, Kaster, Seedorf, Buckel, & Hedderich, ), as the existence of many hydrogen producing Clostridium bacteria and methanogenic archaea in the SFB ecosystem (Ding et al., , , ; Hu et al., ; Li et al., ; Luo et al., ; Tao et al., ; Wu, Ding, Huang, & Zhou, ; Zheng et al., ).…”
Section: Interspecies Interactionsmentioning
confidence: 99%